MENINGKATKAN KEAWETAN JAMU TRADISIONAL SEBAGAI UPAYA OPTIMALISASI PRODUK UNGGULAN DESA KARANGREJO - Khoiriyah Trianti; Sari, Celvia Gusmia; Khasanah, Shofia Uswatul; Imandasari, Rizqi; Cholifah, Junika Nur; Udi, Mohalimas'; Cintya, Oktriaayu Mega (Universitas Muhammadiyah Malang, 2021)
The Village Innovation Program is an assistance carried out to encourage the use of superior products by improving the quality to be even better. Community service for the Covid-19 edition of the PPM Community Service Community Service took place in Karangrejo Village, Kromengan District, Malang Regency. The original inhabitants of Karangrejo Village are the majority of carrying herbal medicine traders. The government's appeal forbids its citizens to do activities outside especially gathering with many people to prevent the transmission of the Covid-19 virus having an impact on the herbal medicine traders. Herbal medicine traders experienced a tremendous impact they could not sell herbal medicine by going around as usual while the herbal medicine only lasted a week. This will also be an obstacle if the herbs are sold online because the shelf life is relatively short. Thus, we provide innovations for herbal medicine packaging so that it can last longer, which is made into herbal powder and packaged in an attractive manner.